2013
DOI: 10.1186/1755-7682-6-35
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory effects of water ingestion during and after exercise

Abstract: BackgroundIn prolonged exercise, the state of hypohydration due to sweating raises physiological stress and induces a drop in sports performance. However, the impact of water intake in cardiorespiratory parameters when administered during and after physical activity has not been well studied. This study aimed to analyze the effects of water intake in heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), partial oxygen saturation (SpO2) and respiratory rate during and after prolonged e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Moreover, there is compelling evidence that it occurs secondarily to sympathetic vasoconstriction resulting from the activation of the transient receptor potential cation channel family (TRPV osmolarity-sensitive Ca 2+ channels) within the portal vein and liver (McHugh et al, 2010;. Previous studies have provided conflicting evidence on whether water ingestion abolishes PEH (Endo et al, 2012;Moreno et al, 2013). Specifically, while one investigation showed no reduction in BP during recovery from 60 min of moderate cycling (Endo et al, 2012), the other observed a significant hypotension after 90 min of moderate running on a treadmill (Moreno et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is compelling evidence that it occurs secondarily to sympathetic vasoconstriction resulting from the activation of the transient receptor potential cation channel family (TRPV osmolarity-sensitive Ca 2+ channels) within the portal vein and liver (McHugh et al, 2010;. Previous studies have provided conflicting evidence on whether water ingestion abolishes PEH (Endo et al, 2012;Moreno et al, 2013). Specifically, while one investigation showed no reduction in BP during recovery from 60 min of moderate cycling (Endo et al, 2012), the other observed a significant hypotension after 90 min of moderate running on a treadmill (Moreno et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided conflicting evidence on whether water ingestion abolishes PEH (Endo et al, 2012;Moreno et al, 2013). Specifically, while one investigation showed no reduction in BP during recovery from 60 min of moderate cycling (Endo et al, 2012), the other observed a significant hypotension after 90 min of moderate running on a treadmill (Moreno et al, 2013). However, as the effects of water intake on resting BP were not controlled for in these studies, interpretations on PEH were mostly substantiated on comparisons between values obtained at resting conditions before water ingestion and those obtained during recovery from exercise postwater ingestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, different strategies to accelerate the autonomic and cardiovascular system recovery after physical exercise practice have been studied on literature [15][16][17][18][19][20] , and water intake is one of than [21][22][23] . Studies that investi-gated the effects of water intake associated to physical exercise, pointed that this strategy was able to attenuate cardiovascular 18,24 and autonomic [20][21][22][23] alterations promoted by the thermic stress as a result of physical exercise and to promote a faster recovery of the organism 18,[20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…They showed that water consumption accelerated cardiac vagal reactivation after exercise; however, no significant influence on heart rate (HR) and blood pressure responses was observed 6 . In another study, the participants were subjected to a protocol of hydration during and after exercise: the results showed minimal changes in systolic blood pressure (SBP) and diastolic blood pressure (DBP) and a smaller increase in HR during exercise 7 . The results showed better HR recovery and faster return of SBP and DBP and better performance of pulse oxygen saturation and respiratory rate.…”
Section: Introductionmentioning
confidence: 99%